IMPLEMENTATION OF THE VIOLENCE ELEMENT WITHIN THE CRIME OF ROBBERY - Adiansyah, Sayib Fauzi; Suyatna, Suyatna (LPPM STIH Putri Maharaja, 2023)
Judges are people who are believed to be representatives of God. Their decisions must always reflect justice for all the litigants, not only by the judge's beliefs but also by the astronomical knowledge of applicable theories and norms. Often, judges make mistakes when they observe almost similar cases, such as case 827/Pid.B/2021/PN.Jmr. The judge could not differentiate between the defendant's actions as theft and violence or an ordinary theft. This study analyzes the extent of the judge's assessment of the degree of violence in the crime of robbery. The research aims to find out how judges assess and determine the degree of violence in criminal acts of theft that involves violence. The research method used is a normative juridical method, referring to the statutory, conceptual, and case approaches, which takes samples of criminal case verdicts in the jurisdiction of the Jember District Court. The research results concluded that the judge was negligent and mistaken in applying the appropriate criminal code article based on legal facts. The defendant's actions were more appropriately said to have committed an ordinary theft as in the subsidiary indictment of the Public Prosecutor because normatively and theoretically, the defendant's actions referred more to the crime of common theft, not theft with violence.